Geospatial Technologies for All Selected Papers of the 21st AGILE Conference on Geographic Information Science (Lecture Notes in Geoinformation and Cartography,, 2018)
This book presents the research papers accepted for the 21st AGILE Conference on Geographic Information Science, held at Lund University Geographical Information Systems (GIS) Centre, Sweden on 12-15 June 2018. It discusses the role of geospatial technologies in the digitalization of society and is intended primarily for professionals and researchers in fields that can benefit from geoinformation - both within and outside the area of geographic information science. .